PENGARUH PENYULUHAN GIZI SEIMBANG MENGGUNAKAN MEDIA VIDEO TERHADAP PENGETAHUAN DAN SIKAP PADA REMAJA - Tika Maulina Kusuma Dewi; Dadang Rosmana; Ichwanuddin Ichwanuddin; Widi Hastuti (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2025)
Adolescence is a period that is vulnerable to nutritional problems. Problems that often occur in adolescents are under-nutrition status and over-nutrition status. These problems will have a negative impact on adolescent health, namely a decrease in concentration of learning. Adolescence is a transition period from childhood to adulthood and at that time adolescents feel responsible and free in determining their own food, no longer determined by parents. Lack of nutritional knowledge, causing adolescents are often wrong in determining which foods will have an impact on its nutritional status later in life. Counseling is an effort to improve knowledge and attitudes. Video media is used as a support and a tool for counseling. The purpose of this study was to determine the effect of providing nutrition counseling with video media on knowledge, and attitudes towards adolescents in class X IPA 6 at SMAN 1 Cimahi, which took place in January 2020. The design of this study was a quasi-experimental design with one group pre-test design model post-test without control group. The number of samples obtained is 23 samples. The results showed that the average score of sample knowledge about balanced nutrition before the intervention was 75.65 and after the intervention 87.82. then the average attitude before the intervention was 35.13 and after the intervention 39.00. Wilcoxon test results show there is an effect of balanced nutrition counseling using video media to knowledge (p = 0,000), attitude (p = 0,000). It can be concluded that there is an effect of counseling by using video media on knowledge and attitudes in adolescents of Class X IPA 6 at SMAN 1 Cimahi.